2018
DOI: 10.17582/journal.aavs/2018/6.12.556.568
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Study the Antibacterial Activity of Bacteriocin against Stenotrophomonas Maltophilia and Evaluation its Synergism with some Antibiotics

Abstract: The core of the study is to screen the inhibitory effect of bacteriocin producing Lactobacillus acidophilus against isolated S. maltophilia and examine whether the combination of bacteriocin with antibiotics showed synergistic or antagonistic interaction. The majority of isolates were resistant to two antibiotics and the isolate coded S19 was resistant to the three antibiotics used, which is consider as multi-drugs resistant isolate and used for the synergy test. Initially, minimum inhibitory concentrations (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…MIC of the clinical pathogens to antibacterial agents was determined by using broth microdilution method 25 . In this study, imipenem from ChemCruz-USA, ceftazidime, ceftriaxone, and cefepime from Awamedica-Iraq were used as antimicrobials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MIC of the clinical pathogens to antibacterial agents was determined by using broth microdilution method 25 . In this study, imipenem from ChemCruz-USA, ceftazidime, ceftriaxone, and cefepime from Awamedica-Iraq were used as antimicrobials.…”
Section: Methodsmentioning
confidence: 99%
“…The MICs of the antibiotics and Ag NP in combination were determined after 24 h of incubation at 37 °C, and the FIC was calculated as follows: Antibiotic A FIC = MIC of antibiotic A in combination/MIC of antibiotic A alone; antibiotic B FIC = MIC of antibiotic B in combination/the MIC of antibiotic B alone; the FICI = FIC of antibiotic A plus the FIC of antibiotic B. The FICI calculated was defined as follows: FICI ≤ 0.5 synergistic effect, 0.5 < FICI < 1 partial synergistic effect, FICI = 1 additive, 2 ≤ FICI < 4 indifferent, and 4 < FICI antagonism 25 , 27 , 28 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Danesh et al [42] showed that haloduracin, a lantibiotic bacteriocin, associated with chloramphenicol displayed a wide spectrum of activity against pathogens such as Enterococcus faecalis, E. faecium, S. aureus and even against different strains of Streptococcus [42]. Recently, the combination of a bacteriocin, produced by Lactobacillus acidophilus, with ceftazidime, imipenem and minocycline antibiotics decreased the required minimal inhibitory concentrations (MICs) values of these antibiotics against a strain of Stenotrophomonas maltophila S19, which was previously shown to be resistant to these three aforementioned molecules [43]. Similarly, Al Atya et al [27] demonstrated the synergetic activities of two class IIb bacteriocins, enterocins DD28 and DD93, associated with kanamycin and erythromycin against a clinical strain of MRSA.…”
Section: Antibiotics and Bacteriocins Constitute Promising Synergistic Combinations For Medical Therapymentioning
confidence: 99%